2021
DOI: 10.1038/s41388-021-01906-2
|View full text |Cite
|
Sign up to set email alerts
|

A SNAI2-PEAK1-INHBA stromal axis drives progression and lapatinib resistance in HER2-positive breast cancer by supporting subpopulations of tumor cells positive for antiapoptotic and stress signaling markers

Abstract: Intercellular mechanisms by which the stromal microenvironment contributes to solid tumor progression and targeted therapy resistance remain poorly understood, presenting significant clinical hurdles. PEAK1 (Pseudopodium-Enriched Atypical Kinase One) is an actin cytoskeleton- and focal adhesion-associated pseudokinase that promotes cell state plasticity and cancer metastasis by mediating growth factor-integrin signaling crosstalk. Here, we determined that stromal PEAK1 expression predicts poor outcomes in HER2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…SNAI2 has been implicated in the diseases of melanocytes development and a variety of cancers ( Cobaleda et al, 2007 ). SNAI2 plays a crucial role in regulating T-cell lineages ( Pioli et al, 2016 ) and cancer cell stemness ( Chen et al, 2021 ; Peng et al, 2022 ), as well as modulating lapatinib resistance in HER2-positive breast cancer ( Hamalian et al, 2021 ) and enhancing 5-fluorouracil sensitivity in colorectal cancer ( Findlay et al, 2014 ). We developed a risk-scoring model for SKCM patients according to seven cuproptosis-related differential genes, using a training set to distinguish between low -risk and high -risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…SNAI2 has been implicated in the diseases of melanocytes development and a variety of cancers ( Cobaleda et al, 2007 ). SNAI2 plays a crucial role in regulating T-cell lineages ( Pioli et al, 2016 ) and cancer cell stemness ( Chen et al, 2021 ; Peng et al, 2022 ), as well as modulating lapatinib resistance in HER2-positive breast cancer ( Hamalian et al, 2021 ) and enhancing 5-fluorouracil sensitivity in colorectal cancer ( Findlay et al, 2014 ). We developed a risk-scoring model for SKCM patients according to seven cuproptosis-related differential genes, using a training set to distinguish between low -risk and high -risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…This subset showed high activity of angiogenesis, hedgehog signaling, epithelial mesenchymal transition, NF-κB pathway, and IL10 signaling, suggesting it had essential roles in the remodeling of cancer immunity and progression. In addition, a published study indicated that INHBA over-expression promotes cell proliferation and may be epigenetically regulated in esophageal adenocarcinoma [42].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they identified that MSCs expressing PEAK1 contribute to the emergence of distinct subpopulations within HER2-positive breast cancer cells characterized by high levels of p-Akt, MCL1, and GRP78, as well as low levels of p-γH2AX and VIM. These subpopulations exhibit resistance to lapatinib and demonstrate enhanced tumorigenic potential both in vitro and in vivo settings 197 .…”
Section: The Role Of Mscs In the Treatment Of Breast Cancermentioning
confidence: 99%